Waste Identification In The Production Process PTC Ceramic Heating Element With Lean Manufacturing Approach At CV. Sulis Keramik - Maylani, Arista; Agusti, Febrina; Nur Diansari, Brillian (LPPM Universitas Duta Bangsa Surakarta, 2024)
A firm called CV. Sulis Keramik makes parts for mosquito mats; these parts come in the shape of PTC heating elements. A kind of positive temperature coefficient thermistor used in heating applications is the ptc heating element. There are still many different waste indicators throughout the production process, which lowers the process's efficacy and efficiency. Defects with a 10% defect rate are among the main issues. Furthermore, there exist other indicators of waste associated with waiting times, transportation, and other wastes. With the use of lean manufacturing techniques, this project seeks to eradicate waste from CV Sulis Keramik ptc heating element production process. Value stream mapping in its current state, waste assessment models, value stream analysis tools, production system improvement, and designing future value stream mapping were all shown in the research's first stage.